The Influence of Celebrity Endorsement on Consumer’s Attitude: A Study Case of Smartphone Brands in Jakarta, Indonesia - Melati, Ina; Indira Budiwan, Teddy; Sarjono, Haryadi (International Journal of Engineering and Technology, 2018)
This study analyzes the effect of celebrity endorsement on consumerâ€™s attitude towards social media advertising as well as the effect of consumerâ€™s attitude towards social media advertising on consumerâ€™s purchase intention of smartphone brands in Jakarta. A survey was conducted on 404 university students in Bina Nusantara University. After conducting exploratory factor analysis (EFA) and multiple-regression analysis, the result indicates that consumerâ€™s attitude towards social media advertising is positively affected by 4 factors: celebrity trustworthiness, celebrity liking, celebrity match-up with product and celebrity familiarity. Attitude towards social media advertising also has a positive impact on consumerâ€™s purchase intention of smartphone brands in Jakarta. Â Â